Physiological Evaluation to Improve Growth and Yield Components of Vicia faba and Phaseolus vulgaris in Libya - Khaled, Saleh A. (Al-Mukhtar Journal of Sciences, 2009)
Biofertilzation ( BF ) + Organic fertilizer ( FYM ) induced a significant effect on the high of two plants . The maximum value of the photosynthetic efficiency as well as chlorophyll ( a ) obtained in both plants treated with biofertilizer . However , the concentration of chlorophyll ( b ) did not differ significant . The number of nodules also, significantly increased in the Vicia faba plant treated with biofertilizer. However, there is no response in Phaseolus vulgaris plants . The number of seeds , total nitrogen and the protein ratio, also significantly increased when both plants were treating with the biofertilizer. The application of such N2-fixer organisms in agronomic practice could have a potential for cultivation of plants , especially in salt affected soil .0